The ICT and New Scenarios for Diversity - Tomé, José Manuel Salum (Advances in Social Sciences Research Journal, 2020)
Research is a process aimed at seeking new knowledge, in this case, it will seek to find alternative ways in the field of new technologies that serve to support special educational needs. Society demands these technological contributions to solve problems and allow man to work with greater ergonomics; the school, a social institution, also needs these resources so that all students can build a functional and meaningful teaching-learning process. The Educational System proposes an education that meets the educational needs of all students; and from these pages it is intended that new technologies are a way of supporting that attend to diversity.